Student reactions to learning with technologies perceptions and outcomes - Moyle, Kathryn; Wijngaards, Guus, 1949-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"This book brings together recent research findings about the views and expectations of students when including technologies in their studies, suggesting that the use of technologies in teaching not only makes learning more interesting but also offers possibilities for variations in the learning processes"--Provided by publisher.
1. Students' views about learning with technologies: a literature review / Kathryn Moyle, Guus Wijngaards and Susanne Owen -- 2. New technologies, new horizons: graduate student views on creating their technological pedagogical content knowledge (TPACK) / Hiller A. Spires, Meixun Zheng and Manning Pruden -- 3. What are Alberta's K-12 students saying about learning with technologies? / Bette Gray, Karen Andrews, and Susan Schroeder -- 4. "A community of opinion and debate": postgraduate students' reactions to compulsory online discussions / Elizabeth A. Beckmann -- 5. Learning in a virtual world: student perceptions and outcomes / Sue Gregory -- 6. Student voices and digital technologies in Australian school education / Bernard Brown -- 7. Learning with technologies: perceptions and outcomes in China / Anne Campbell -- 8. Views of students on learning with technologies in Dutch education and training / Pieter Swager and Jeroen Bottema -- 9. Perceptions of marginalized youth on learning through technologies / Jean Johnson, Jonny Dyer and Ben Lockyer -- 10. Students' views of E-learning: the impact of technologies on learning in higher education in Ireland / Eileen O' Donnell and Mary Sharp -- 11. Study and non-study related technologies use of Flemish students in higher education / Steven Bruneel ... [et al.] -- 12. Social learning sites?: Using students' views to explore the use and possibilities of facebook for educational purposes in Flanders / Mathias Decuypere and Steven Bruneel -- 13. The transfer value of successful learning practices using Web 2.0 / Jos Fransen and Bas van Goozen.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed October 21, 2011).
Keywords: Educational technology -- Psychological aspects; Education -- Effect of technological innovations on; Students -- Attitudes; Asynchronous online discussions; Compulsory online discussions; Ethics; Learning in virtual worlds; Mobile learning; Social learning sites; Web 2.0; Technological Pedagogical Content Knowledge (TPACK); Electronic books